Male bladder outlet obstruction: Time to re‐evaluate the definition and reconsider our diagnostic pathway? ICI‐RS 2015. Issue 4 (April 2017) - Rademakers, Kevin; Drake, Marcus J.; Gammie, Andrew; Djurhuus, Jens C.; Rosier, Peter F.W.M; Abrams, Paul; Harding, Christopher
Abstract : The diagnosis of bladder outlet obstruction (BOO) in the male is dependent on measurements of pressure and flow made during urodynamic studies. The procedure of urodynamics and the indices used to delineate BOO are well standardized largely as a result of the work of the International Continence Society. The clinical utility of the diagnosis of BOO is however, less well defined and there are several shortcomings and gaps in the currently available medical literature. Consequently the International Consultation on Incontinence Research Society (ICI‐RS) held a think tank session in 2015 entitled "Male bladder outlet obstruction: Time to re‐evaluate the definition and reconsider our diagnostic pathway?" This manuscript details the discussions that took place within that think tank setting out the pros and cons of the current definition of BOO and exploring alternative clinical tests (alone or in combination) which may be useful in the future investigation of male patients with lower urinary tract symptoms. The think tank panel concluded that pressure‐flow studies remain the diagnostic gold‐standard for BOO although there is still a lack of high quality evidence. Newer, less invasive, investigations have shown promise in terms of diagnostic accuracy for BOO but similar criticisms can be levelled against these tests. Therefore, the think tank suggests further research with regard to these alternative indicators to determine their clinical utility.